PENINGKATAN KEMAMPUAN PEMBAGIAN PESERTA DIDIK KELAS IIIA SDN NGADIREJO 01 DENGAN MEDIA CONGKLAK - Abdul Hafiizh Abyan Prasetya; Siti Nafi’atussholikah; Vina Khoirunisya; Wahdan Najib Habiby (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low basic division skills at SDN Ngadirejo 01 Kartasura. This is due to the lack of learning media and also learning is dominated by teachers. So that student activities are limited which results in low basic division skills. Therefore, this research was conducted to improve basic division skills using congklak game media with 28 students. This research method uses Classroom Action Research (CAR) which is carried out in two cycles. Each cycle has four phases consisting of planning, action, observation, and reflection. Data collection techniques in the form of tests and observations and interviews. The results of the study showed that students' division skills increased in each cycle. This increase is based on the results of the students' numeracy test. This is evidenced by the first cycle, the students' division skills, namely 31%, were categorized as lacking and in the second cycle, the students' division skills, namely 83%, were categorized as good and stated that basic division learning through congklak games had achieved the minimum completion criteria or were declared successful. Therefore, the results of the study prove that the application of congklak game media can improve students' abilities in mathematics subjects in basic division material for class 3 SDN Ngadirejo 01 Kartasura so that congklak games can be used as learning media.